Cassava flour processors in Democratic Republic of Congo have increased their production capacity, incomes, and profitability by using the Efficient Small-scale Flash Dryer innovation - Tran, Thierry Van Kin; Taborda Andrade, Luis Alejandro (2023)
An efficient small-scale flash drying technology was scaled out from 2019 to 2022 by the CGIAR team CIAT-CIRAD-IITA. The innovation was adopted by 5 cassava flour processors and 1 equipment manufacturers from D.R. Congo. This flash drying innovation package has positively impacted the environment and considerably increased the profitability of cassava processing, as the processors doubled to tripled their production capacity, and cut their fuel consumption per ton of cassava flour produced by 30 to 50%.